Factors Of Using The Spiritual Heritage Of Great Teacher Scientists In The Development Of Students' Educational Research Competences (Journal of Pedagogical Inventions and Practices, 2024)
This article describes the use of the heritage of great mudarris scientists in the development of students' educational research competencies.